2014
DOI: 10.1158/0008-5472.can-13-3634
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drug Formulation on OATP1B-Mediated Transport of Paclitaxel

Abstract: Purpose Taxane antineoplastic agents are extensively taken up into hepatocytes by OATP1B-type transporters prior to metabolism and excretion. Because the biodistributional properties imposed upon these agents by different solubilizers drive clinically-important pharmacodynamic endpoints, we tested the hypothesis that the in vitro and in vivo interaction of taxanes with OATP1B transporters is affected by the choice of drug delivery system. Experimental Design Transport of paclitaxel, docetaxel, and cabazitaxe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 48 publications
(62 reference statements)
9
49
2
Order By: Relevance
“…Indeed, transmembrane transport of taxanes is now widely acknowledged to be mediated by specific OATPs. In particular, we previously reported that paclitaxel and docetaxel are transported substrates of human OATP1B1 (SLCO1B1) and OATP1B3 (SLCO1B3) (14)(15)(16)(17), as well as the single functional homolog OATP1B2 (Slco1b2) in mice (18) and rats (18,29). These findings have been independently verified (30)(31)(32)(33)(34), and are consistent with in vitro studies that have identified paclitaxel as a potent inhibitor of OATP1B1-(35, 36) and OATP1B3-mediated transport (35,37,38).…”
Section: Oatp1b2 As a Putative Paclitaxel Transporter In Mouse Neuronssupporting
confidence: 86%
See 3 more Smart Citations
“…Indeed, transmembrane transport of taxanes is now widely acknowledged to be mediated by specific OATPs. In particular, we previously reported that paclitaxel and docetaxel are transported substrates of human OATP1B1 (SLCO1B1) and OATP1B3 (SLCO1B3) (14)(15)(16)(17), as well as the single functional homolog OATP1B2 (Slco1b2) in mice (18) and rats (18,29). These findings have been independently verified (30)(31)(32)(33)(34), and are consistent with in vitro studies that have identified paclitaxel as a potent inhibitor of OATP1B1-(35, 36) and OATP1B3-mediated transport (35,37,38).…”
Section: Oatp1b2 As a Putative Paclitaxel Transporter In Mouse Neuronssupporting
confidence: 86%
“…Following this chronic regimen, we found that OATP1B2 -/-mice were also protected against paclitaxelinduced thermal hyperalgesia ( Figure 2E) and changes in digital nerve maximal action potential amplitude (AMP) ( Figure 2F). In support of a functional involvement of OATP1B2 in the paclitaxelinduced toxicity, it is noteworthy to point out that the taxane cabazitaxel, the usage of which is very rarely associated with peripheral neuropathy (22), is not transported by OATP1B-type carriers (18).…”
Section: Oatp1b2 As a Putative Paclitaxel Transporter In Mouse Neuronsmentioning
confidence: 96%
See 2 more Smart Citations
“…Iusuf and colleagues recently found that OATP1A2 was also involved in the in vivo uptake of docetaxel [10]. Animal studies with the OATP1B3/OATP1B1 orthologue OATP1B2 showed that the CL of docetaxel is substantially decreased in OATP1B2 knockout mice [8,10,20,21] in a manner that resembles drug phenotypes observed in mice with a deficiency of metabolic Cyp3a activity [22]. Therefore, co-medication that inhibits both OATP1B1 and 1B3 should only be used with caution in combination with docetaxel.…”
Section: Hepatic Uptakementioning
confidence: 99%